Epithelioid angiomyolipoma of the kidney in an adult male with tuberous sclerosis - Nada Shaker; Douglas Wu; Anil Parwani (Urology Case Reports, 2022)
Epithelioid angiomyolipoma is a rare variant of angiomyolipoma and a part of the microphthalmia transcription factor (MiTF) tumors. We report a case of epithelioid angiomyolipoma of the kidney that occurred in a 40-year-old male. The tumor was composed of sheets of uniform epithelioid cells with clear to granular eosinophilic cytoplasm and hyperchromatic nuclei. The tumor extended into the vascular margin and perinephric fat with identified angiolymphatic invasion. Immunohistochemistry showed diffuse staining for HMB45, Melan A, and focal staining for SMA. No expression for EMA, AE1/AE3, CK7, S100, or Desmin was noted. The patient underwent a left nephrectomy with no recurrence.